2020
DOI: 10.5009/gnl18573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Biliary Drainage during a Neoadjuvant Therapy for Pancreatic Cancer: Metal versus Plastic Stents

Abstract: Neoadjuvant chemotherapy/neoadjuvant chemoradiotherapy (NAC/NACRT) can be performed in patients with pancreatic cancer to improve survival. We aimed to clarify the clinical outcomes of biliary drainage with a metal stent (MS) or a plastic stent (PS) during NAC/NACRT. Between October 2013 and April 2016, 96 patients with pancreatic cancer were registered for NAC/NACRT. Of these, 29 patients who underwent biliary drainage with MS or PS before NAC/NACRT and a subsequent pancreatoduodenectomy were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 27 publications
2
38
1
Order By: Relevance
“…Therefore, CMS should be avoided in cases of distal cholangiocarcinoma, papillary carcinoma, and pancreatic cancer where the diagnosis is uncertain. The time to RBO after preoperative PS (7 Fr or 8.5 Fr) implantation has been reported as approximately 50-63 days 6,10,11 and was 40 days in this study. It is difficult to maintain stent patency with PS alone during the preoperative waiting period, which is about 5 months and may include radiotherapy.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Therefore, CMS should be avoided in cases of distal cholangiocarcinoma, papillary carcinoma, and pancreatic cancer where the diagnosis is uncertain. The time to RBO after preoperative PS (7 Fr or 8.5 Fr) implantation has been reported as approximately 50-63 days 6,10,11 and was 40 days in this study. It is difficult to maintain stent patency with PS alone during the preoperative waiting period, which is about 5 months and may include radiotherapy.…”
Section: Discussionsupporting
confidence: 51%
“…Our findings show that the CMS was superior to the PS for biliary decompression during NAC-RT, with respect to RBO. 10,11 This study is the largest single-center comparison of stents used for biliary drainage in patients with pancreatic cancer undergoing NAC-RT. Furthermore, in this study, there was no difference in the surgical results, such as operation time, blood loss, and the R0 resection rate between the CMS and PS groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Many previous studies on biliary drainage for patients with unresectable pancreatic cancer indicated that a metal stent is superior to a plastic stent in terms of patency 9 ; however, a few recent studies also revealed longer patency and lower cost related to the stent occlusion of a metal stent than those of a plastic stent during NAC/NACRT. [10][11][12][13][14] It remains controversial which type of self-expandable metal stent (SEMS) is the most suitable for patients with resectable or borderline resectable pancreatic cancer during NAC/NACRT: an uncovered SEMS (USEMS), fully covered SEMS (FCSEMS) or partially covered SEMS (PCSEMS). During NAC/NACRT in patients with pancreatic cancer, the USEMS has been the standard SEMS for biliary decompression as well as during chemotherapy in patients with unresectable pancreatic cancer, but there have been few comparative studies on the patency and safety of SEMSs in curative surgery after neoadjuvant therapy.…”
Section: Open Accessmentioning
confidence: 99%
“…[43][44][45] For patients undergoing NAT, SEMS were either equivalent to or superior to PS, and some studies describe fewer delays to NAT initiation. 42,46,47 Uncovered versus Covered Self-Expanding Metal Stents Uncovered SEMS allows for tissue ingrowth into the stent struts, which anchors the stent in place and helps prevent stent migration. This ingrowth can also result in stent occlusion and makes it difficult or impossible to exchange or remove the stent in case of occlusion or if no longer desired.…”
Section: Plastic Stents Versus Self-expanding Metal Stentsmentioning
confidence: 99%